Exploring the Effect of Frictional Heat on Rate of Fuel Combustion by ICE through Modeling and Simulation with Reference to ICE Parameters. - Festus, Motey; Hagan, Essel Ben (Archives of Business Research, 2017)
Otto cycle operations of ICEs have relatively higher capacities and efficiency. Factors of efficiency, emission, fuel consumption and output power are considered during design and construction of ICEs. Engine size, engine weight, number of pistons, swept volume, cylinder arrangement and number of valves all differs in accordance to type of ICE. Fundamental principle of ICE is burning of air – fuel mixture of appropriate proportions in air tight chamber to produce heat energy for motion. Fossil fuel of diesel and gasoline obtained from underground are the main fuels used by ICEs. The engine block houses cylinders, pistons rings, connecting rods and pistons. At top seals of cylinders are located inlet valves, outlet valves and channels. Crankcase houses crankshaft and bearings whiles the sump serves as reservoir for lubrication oil. Lubrication oil also known as lubricant reduces friction between moving surfaces in ICEs through piston ring grooves. Connecting rod is the linkage between crankshaft and piston. Gudgeon – pin transmits combustion force from piston to connecting rod then to crankshaft. Thus, crankshaft converts reciprocating motion of piston to cyclic motion. During operations of ICEs, friction occurs between pistons with piston rings collectively and inner walls of cylinder. Frictional effects account for about thirty five percent (35%) of total heat generated in ICEs. The methodology adopted by this article is modeling and simulating frictional models by previous authors. These models were incorporated with ICE parameters before modeling and simulation again. Objectively, graphical results show reduction in heat generation due to friction.